2003
DOI: 10.1038/sj.pcan.4500654
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral electrovaporization of the prostate (TUVP) is effective, safe and durable

Abstract: Transurethral electrovaporization of the prostate (TUVP) is one of the alternative, minimally invasive procedures to treat BPH with promising initial results. We reviewed the available English literature to evaluate the long-term safety, efficacy and durability of TUVP using various vaporizing electrodes. We performed a MEDLINE keyword search and assessed all prospective randomized studies, which compared TUVP to standard transurethral resection of the prostate (TURP) that reached 1 y follow-up. Data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…urine leak, haematoma, undue tension). (10) Risk factors for BNC development after prostatectomy include a history of diabetes mellitus, coronary artery disease, obesity, surgeon experience, surgical technique and certain postoperative complications (haemorrhage, prolonged urine leak, anastomotic disruption) (11) ; nevertheless, in our study one patient developed bladder neck contracture after open prostatectomy. This patient had diabetes mellitus and hypertension as risk factors.…”
Section: Discussionmentioning
confidence: 61%
“…urine leak, haematoma, undue tension). (10) Risk factors for BNC development after prostatectomy include a history of diabetes mellitus, coronary artery disease, obesity, surgeon experience, surgical technique and certain postoperative complications (haemorrhage, prolonged urine leak, anastomotic disruption) (11) ; nevertheless, in our study one patient developed bladder neck contracture after open prostatectomy. This patient had diabetes mellitus and hypertension as risk factors.…”
Section: Discussionmentioning
confidence: 61%
“…Of note, TURP was the only intervention in this trial with a durable improvement in Qmax. Two studies describing shorter 5-year follow-up demonstrated similar results, with the exception that the improvement in Qmax remained significant [19,20]. Reoperation rates and postoperative PVR were higher for TUVP than TURP in the randomized trial by Hammadeh et al [13].…”
Section: Transurethral Electrovaporizationmentioning
confidence: 63%
“…Transurethral electrovaporization (TUVP) was first described by Bush et al [18] in 1993 with the potential advantages of reduced bleeding and TUR syndrome [19]. Hoekstra et al [6••] reported 10-year follow-up data from a randomized control study comparing TURP, TUVP, and CLP, including 48 patients treated with TUVP.…”
Section: Transurethral Electrovaporizationmentioning
confidence: 99%
“…Zahvat se izvodi uz ispiranje fiziološkom otopinom, što smanjuje nastanak TUR sindroma. Pokazalo se kako je trajanje poslijeoperativne kateterizacije nakon TUVP-a kraće te da su kratkoročni rezultati TURP-a i TUVP-a usporedivi, međutim potrebne su bolje dizajnirane studije za usporedbu dugoročnih rezultata 20 .…”
Section: Transuretralna Vaporizacija Prostateunclassified